Religious Authority and Social-Political Dynamics in National Awakening Party Candidate Recruitment Reform - Sugiarto, Sugiarto; Alfirdaus, Laila Kholid; Martini, Rina (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the dynamics of PKB Central Java’s open recruitment mechanism for legislative candidates in the 2024 election and analyzes whether the reform contributed to substantive internal democratization. Using a qualitative case study design, data were collected through in-depth interviews with party officials, aspirants, and local brokers across Pati, Rembang, and Kudus, complemented by document analysis of recruitment guidelines, interview evaluations, and administrative procedures. The findings show that the reform generated a form of hybrid openness: while the process expanded access, standardized interviews, and increased procedural transparency, final decisions remained strongly shaped by longstanding NU-based religious authority, particularly kyai endorsements and pesantren networks. Meritocratic tools such as interview scoring and documentation review enhanced procedural clarity but carried limited weight in determining rankings, reflecting selective meritocracy rather than full institutional transformation. The study also reveals significant district-level variation, with Kudus exhibiting greater alignment between assessment outcomes and final placement compared to the more hierarchical environments of Pati and Rembang. These patterns position PKB’s reform between symbolic and substantive democratization, producing visible improvements without altering deeper authority structures. The study contributes to the literature on internal party democracy by demonstrating how socioreligious legitimacy, territorial power structures, and institutional layering shape the outcomes of organizational reform in Islamic-oriented political parties in Indonesia.